Primary second molar relations in preschool-aged children - Arifin, Rafinus; Hidayatullah, Taufiqi; Rahayu, Sholeha (Padjadjaran Journal of Dentistry, 2018)
Introduction: The primary second molar relation is also called the terminal plane, which is the relation between the distal surface of the maxillary and mandibular second primary molars in a centric occlusion position. One of the most important characteristics of the ideal occlusion development on the primary dentition is if the primary second molar relation classified as the flush terminal plane. This relation plays a significant role in determining the relation in permanent molar because the eruption of the first permanent molars are guided by the distal surface of the maxillary and mandibular second primary molars. The purpose of this study was to found out the clinical description of the primary second molar relation among the preschool-aged children in four kindergartens in Banda Aceh. Methods: This study was a descriptive study with cross-sectional study approach. The subject selection method was performed with a purposive sampling method involving as much as 37 subjects, which wereÂ studentsÂ of State Kindergarten of Pembina 1, State Kindergarten 2, State Kindergarten 3, and State Kindergarten of Adidarma 4, Banda Aceh. The examination was performed by using the intraoral mirror when the teeth were in the centric occlusion position. Decisions regarding the primary second molar relation were made by the bilateral occlusion (left and right). Results: The flush terminal plane was found in 45.9% of all respondents, the mesial step was 54.1%, and the distal step was 0.0%. Conclusion: The primary second molar relation among preschool-aged children generally had the mesial step.